The Fragmented Self: Having Multiple Accounts in Instagram Usage Practice among Indonesian Youth - Mashita Phitaloka Fandia Purwaningtyas; Desti Ayu Alicya (Universitas Gadjah Mada, 2020)
The usage of social media has become a part of youth’s life in this digital era. Particularly in Indonesia, Instagram is one of the most popular platforms among youth. In the practice of Instagram usage, apparently a person could manage more than just one account, creating phenomenon known as ‘real Instagram account’ and ‘fake Instagram account’. Hence this form of practice is raising question in regards to the identity presented by users in those accounts. This paper aims to analyze the practice of having multiple accounts in Instagram platform, focusing on how the self-presentation of users presented and why such presentation displayed, specifically in the contestation between the concept of ‘real’ and ‘fake’. Scope of the study in this research covers the media psychology of interconnection between self and social media platform. Research was conducted by mixed-method of new ethnography and virtual ethnography. Expected findings in this research include the analysis of fragmented self in Instagram multiple accounts, focusing in the issue of how the concept of ‘real’ and ‘fake’ are being defined by users, and the aspects behind such understandings. Apparently, in the social media platform as Instagram, youth is in search for a sense of freedom and authenticity, where they could be free in expressing themselves. Thus, the motivation of having multiple accounts. However, findings in this research also indicate that certain standards have been created in the Instagram, that at some point to some extent have conditioned users to present themselves in certain ways.